2017
DOI: 10.3390/land6010002
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Benefits of Tropical Multifunctional Land-Uses in and Around a Forest Protected Area of Bangladesh

Abstract: Abstract:Competing interests in land for agriculture and commodity production in tropical human-dominated landscapes make forests and biodiversity conservation particularly challenging. Establishment of protected areas in this regard is not functioning as expected due to exclusive ecological focus and poor recognition of local people's traditional forest use and dependence. In recent years, multifunctional land-use systems such as agroforestry have widely been promoted as an efficient land-use in such circumst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Mukul et al [11] measured the conservation value of four local agroforestry land uses and the forest itself, in and around a protected forest in Bangladesh. They found that agroforestry can complement the protected area.…”
mentioning
confidence: 99%
“…Mukul et al [11] measured the conservation value of four local agroforestry land uses and the forest itself, in and around a protected forest in Bangladesh. They found that agroforestry can complement the protected area.…”
mentioning
confidence: 99%
“…For example, a win-lose link ensues when deforestation cost borne by a society for its development as forest resources are turned in to satisfy agricultural requirements [25]. The increase in agricultural production has driven the change and deterioration of tropical forests [15,17,29]. An ideal win-win relationship is when forests are allowed to regenerate to ensure adequate ground cover to achieve an appropriate landscape without compromising ecosystem integrity [25].…”
Section: Conceptual and Analytical Frameworkmentioning
confidence: 99%
“…The selective cutting down of indigenous trees for tobacco production is a case in point here. This is characterized by an alteration of the species composition, even leading to biodiversity loss which is seen as a pervasive global environmental threat [15,16,45]. This difficult situation also results from the inherent changes of the ecosystems and the shifting human relations driven by the prevailing socioeconomic fundamentals and systems of rules [42].…”
Section: Conceptual and Analytical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of climate change greatly threat agriculture productions and food security more in many developing countries (Cotter and Tirado, 2008). Moreover, conflicts of interests between conservationist and agriculture sectors on biodiversity reserve area were intensified in tropical human-dominated landscapes (Mukul and Saha, 2017). The above all indicated that conservation of biodiversity (both flora and fauna) merely in natural reserve is proved to be difficult.…”
Section: Introductionmentioning
confidence: 99%